Implementasi Peraturan Daerah Nomor 4 Tahun 2023 Tentang Pengelolaan Sampah Di Pesisir Kecamatan Galesong Utara Kabupaten Takalar - Nurul Sifa; Fatmawati Fatmawati; Riskasari Riskasari (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the implementation of Regional Regulation Number 4 of 2023 concerning waste management in the coastal area of Galesong Utara District, Takalar Regency. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that policy implementation is influenced by four main aspects: communication, resources, implementers’ disposition, and bureaucratic structure. Socialization and inter-agency coordination play crucial roles in enhancing public awareness and participation. However, several challenges remain, including limited facilities, human resources, and financial support. Despite these obstacles, implementers consistently strive to strengthen community involvement in coastal waste management. The study concludes that the effectiveness of waste management depends on strong collaboration, transparent communication, adequate resources, a committed implementing apparatus, and an efficient bureaucratic framework that supports sustainable coastal governance.